I'm pretty sure it is.
If i'm wrong, I'm truly sorry
(n*3)+6-(n*2)=n+3
3n+6-2n=n+3
3n-2n-n=3-6 every n on the left and free numbers on the right
0=-3
contradiction, there are no solution
Answer:
Step-by-step explanation:
Answer:
x = t(a+p)/4
Step-by-step explanation
Given the expression
a=4x/t - p
We are to make x the subject of the formula
a=4x/t - p
Add p to both sides
a+p = 4x/t - p+p
a+p = 4x/t
Cross multiply
t(a+p) = 4x
Rearrange
4x = t(a+p)
Divide both sides by 4
4x/4 = t(a+p)/4
x = t(a+p)/4
Answer:
A
Step-by-step explanation:
I think it's A because it mostly multiplies then adds and subtracts so you get your answer doing this